Modernization practices and Operating Models: An Empirical Study on a Retail Bank in Sri Lanka - S M Chaturika Seneviratne; Sandani Gunawardane (Goodwood Publishing, 2022)
Purpose: The purpose of this research is to investigate how modernization practices adopt concerning operating models, to comprehend how a retail bank has responded to such transformations, and to investigate the challenges in executing modernization strategies in a Sri Lankan local bank. Research methodology: This study was conducted according to a qualitative single-case study at one leading licensed-commercial bank in Sri Lanka. Data was gathered from semi-structured interviews, direct observations, and archival documents. Results: The findings revealed that unprecedented changes in customer behavior, fierce competition, and capitalizing on capabilities for surviving a dynamic operational landscape were the factors that led a bank to adopt modernization. Limitations: As the study narrowed down to one leading retail bank, it does not cover modernization initiatives offered within the other services portfolio in the banking industry. Contribution: The findings assist professionals to understand the need for modernization of a retail bank’s operating model and thereby formulate strategies in order to capture the benefits of such a transformation.